Genesis and evolution of the valle del Sibundoy soils (2017)
Soil genesis comprises the study of factors and processes involved in soil formation; it is the synthesis and explanation to why the soils exist, their characteristics and distribution. Understanding the genesis, evolution, mineralogy, and current state of soils is fundamental for productive land management and conservation of strategic zones. The Valle del Sibundoy, located northwestern Putumayo, has an approximate area of 9100 ha (ICAC, 2014); in this area, a soil survey was conducted at a semi-detailed scale to determine the factors governing the soils origin, and infer the processes that have occurred and have left marks in the soil profile. A sampling system of rigid network was designed; first 402 trunks were distributed every 25 ha approximately, and then 71 modal profiles were characterized. Based on field and laboratory data, it was concluded that the factors governing the geo—genesis in the study area are, in the first instance, the topography, secondly the parental material, and thirdly the climate and the action of organisms over time. Furthermore, three specific evolutionary processes were identified: Andisolization, Paludization and Gleization, which were corroborated by micromorphological analysis.